TRANSACTIONS IN LAND IN THE SUBURBAN ZONE OF BYDGOSZCZ OVER THE YEARS 2007–2010 - Głębocki, Benicjusz; Perdał, Robert (Quaestiones Geographicae, 2013)
This article offers a spatial analysis of transactions in land seen against the resources of land and its use pattern in the Bydgoszcz suburban zone over the years 2007-2010. The research covered individual transactions aggregated into geodetic precincts by type of land. Its object was the most popular types of land, viz. farmland, built and unbuilt urbanised land, and recreational land. The analysis embraced the number of sale/purchase transactions concluded, the mean area of lots, and their market value.